Clinic panel information system: case study of international students in Universiti Utara Malaysia - Farhan, Mohammed Jaber; Muhisn, Sinan Adnan; Al-khafaji, Nassir Jabir; Muhisn, Zahraa Abed Aljasim (JMEST, 2016)
Health service is one of the important services offered by universities to international students. It is considered a significant measure that indicates the universities’ interest in the welfare of this segment of students.However, obstacles related to health service negatively affect students, and one of these obstacles is the requirement to present health insurance documents.Generally, hospitals require students to show proof of health insurance prior to treatment.This requirement is a challenge for students especially in emergency cases, and it also delays the therapy or surgery.In response to this issue, this paper aims to develop a prototype of clinic panel information system that allows online access to student information, including their insurance details, and sends e-mail notifications to students when their insurance is about to expire.Rapid application development methodology is used in research design, and system usability scale was used to evaluate the usability.The prototype was assessed through a sample that consists of thirty-six respondents and was found to produce positive results.